The Investigation of the Effect of Static and Dynamic Core Training on Performance on Football Players - Akan Bayrakdar; Hilal Kılınç Boz; Ömer Işıldar (Türk Spor ve Egzersiz Dergisi)
This study was carried out to investigate the effect of static and dynamic core training on the performance of football players. In this study, static and dynamically applied core exercises were evaluated in terms of speed and agility in football players, and then their effects on anaerobic power tests, core stabilization tests and body composition were compared. While 10 of the 30 football players participating in the study were practicing dynamic core exercises and 10 of them were practicing static core exercises 2 days a week for about 9 weeks and 30 minutes a day, 10 athletes continued their football training with the other group athletes as control groups. The effects of the exercises, performed at the end of 9 weeks on performance, body composition, and core stabilization tests were compared in the pre and post-test in order (p lt;0.05). There is no significant difference in the height, body weight, body mass index parameters of 30 subjects (10 control, 10 static core, 10 dynamic core) belonging to the 3 groups participating in the study. Significant differences were found at waist level and hip circumference at the level of p lt;0.05 in comparisons between the first and last measurements of all anthropometric measurements. While there was a significant increase in the duration of leg lift, push-up, plank, shuttle, and isometric tests, a decrease was observed in the plank, shuttle and isometric test times in the control group. In the pre and post-test comparisons, 30 m speed, long jump, vertical jump, agility 550 and arrowhead agility tests showed a significant difference at p lt;0.05 level. It can be said that core studies should be included in training aimed at increasing performance in the football branch.